GLOWORM-PARA: a flexible framework to simulate the population dynamics of the parasitic phase of gastrointestinal nematodes infecting grazing livestock. Issue 2 (February 2020) - Rose Vineer, H.; Verschave, S.H.; Claerebout, E.; Vercruysse, J.; Shaw, D.J.; Charlier, J.; Morgan, E.R.
Graphical abstract: Highlights: The transmission of gastrointestinal nematode parasitic stages was modelled. The generic model was parameterised for Cooperia oncophora and Ostertagia ostertagi in cattle. Extensive validation using field data demonstrated good model performance. A pragmatic approach to modelling data-sparse systems (immunity) is demonstrated. Stochastic parameters can be introduced to incorporate host variability. Abstract: Gastrointestinal nematodes are a significant threat to the economic and environmental sustainability of keeping livestock, as adequate control becomes increasingly difficult due to the development of anthelmintic resistance in some systems and climate-driven changes to infection dynamics. To mitigate any negative impacts of climate on gastrointestinal nematode epidemiology and slow anthelmintic resistance development, there is a need to develop effective, targeted control strategies that minimise the unnecessary use of anthelmintic drugs and incorporate alternative strategies such as vaccination and evasive grazing. However, the impacts climate and gastrointestinal nematode epidemiology may have on the optimal control strategy are generally not considered, due to lack of available evidence to drive recommendations. Parasite transmission models can support control strategy evaluation to target field trials, thus reducing the resources and lead-time required to develop evidence-based control recommendations incorporating climate stochasticity. Gastrointestinal nematode population dynamics arising from natural infections have been difficult to replicate and model applications have often focussed on the free-living stages. A flexible framework is presented for the parasitic phase of gastrointestinal nematodes, GLOWORM-PARA, which complements an existing model of the free-living stages, GLOWORM-FL. Longitudinal parasitological data for two species that are of major economic importance in cattle, Ostertagia ostertagi and Cooperia oncophora, were obtained from seven cattle farms in Belgium for model validation. The framework replicated the observed seasonal dynamics of infection in cattle on these farms and overall, there was no evidence of systematic under- or over-prediction of faecal egg counts. However, the model under-predicted the faecal egg counts observed on one farm with very young calves, highlighting potential areas of uncertainty that may need further investigation if the model is to be applied to young livestock. The model could be used to drive further research into alternative parasite control strategies such as vaccine development and novel treatment approaches, and to understand gastrointestinal nematode epidemiology under changing climate and host management.